The conquerors Roosevelt, Truman, and the destruction of Hitler's Germany, 1941-1945 - Beschloss, Michael R (Simon & Schuster, 2003)
The Conquerors provides a fascinating insight into the behind-the-scenes negotiations during World War II that led to the emasculation of Germany. As Presidents Roosevelt and Truman led the United States in World War II in Europe, they had to deal with the question of what kind of government should be imposed on Nazi Germany to ensure that Germany could never again drag the world into war. The Conquerors tells the story with much intimate detail and colour of how Roosevelt and Truman privately struggled in their own minds and with titanic allies like Winston Churchill and Josef Stalin, through summits and secret messages, to answer this question. Roosevelt did not react to increasing evidence of the Holocaust, but close friend and Secretary of the Treasury, Henry Morgenthau, Jr., privately pressed Roosevelt to accept what was soon called the "Morgenthau plan" - teach the Germans a lesson and destroy their ability to make war by destroying their industrial base and letting many Germans starve to death. Bechloss also revels how Harry Truman, on abruptly assuming the Presidency, was briefed on the Morgenthau Plan and was appalled. Truman, backed by Cabinet members, turned his back on the plan, fired Morgenthau, and moved toward Germany's division between East and West, allowing West Germany to become the bulwark of Western opposition to Soviet expansionism in Europe.